OSCILLATION PROPERTIES OF SOLUTIONS OF FRACTIONAL DIFFERENCE EQUATIONS - Bayram, Mustafa; Secer, Aydin (VINCA INST NUCLEAR SCI, 2019)
In this article, studied the properties of the oscillation of fractional difference equations, and we obtain some results. The results we obtained are an expansion and further development of highly known results. Then we showed them with examples.
Keywords: fractional difference equation; oscillatory solutions; oscillation theory; CRITERIA; Thermodynamics